Quantifying local TB risk factors and determining the relative cost of treatment of latent TB infection to prevent tuberculosis. Issue 4 (2nd October 2017) - Ward, Heather; Stewart, Samuel; Al-Azem, Assaad; Reeder, Bruce; Hoeppner, Vernon
ABSTRACT: RATIONALE: The risk of tuberculosis (TB) disease in tuberculin skin test positive (TST+) persons ranges from 5–15%. National averages of risk mask local variation. OBJECTIVE: Quantify local TB disease risk and the cost of preventing one case of TB disease with treatment of LTBI. METHODS: Saskatchewan persons with a first TST+ recorded from January 1, 1986 to January 31, 2002 were reviewed for progression to TB by ethnic origin, age, sex, and interval from first TST+ to TB. From this risk the cost to prevent one case of TB disease was determined for each group. RESULTS: The cumulative incidence of TB in 11, 698 persons after first TST+ was 6.2%. There was variability in incidence density by ethnic origin (0.6–15.2), age (2.4–33.9), sex (4.7–9.2), and recent vs. remote interval to TB disease (1.3–1667). The cost to prevent one case of TB disease in non-Indigenous people ≥20 years with remote infection compared to Indigenous people <20 years with recent infection was higher by a factor of >200. CONCLUSIONS: Progression from first TST+ to TB disease varied by age, ethnicity, and interval from TST+ to TB disease but not by sex. The cost to prevent one case of TB disease varied inversely. Using local epidemiological data is useful and simple to quantify risk of TB disease and cost to achieve best prevention for each dollar spent. RÉSUMÉ JUSTIFICATION: Le risque de tuberculose chez les personnes ayant obtenu un résultat positif au test cutané à la tuberculine (TCT) se situe entre 5 et 15 %. Les moyennes nationales occultent les variations locales. OBJECTIF : Quantifier le risque local de tuberculose et le coût de prévention d'un cas de tuberculose par le traitement de l'ITL. MÉTHODES: Les personnes de la Saskatchewan ayant obtenu un premier résultat positif à un TCT entre le 1 e janvier 1986 et le 31 janvier 2002 ont été revues pour mesurer l'évolution vers la tuberculose en fonction de l'origine ethnique, de l'âge, du sexe et de l'intervalle entre le premier TST positif et l'apparition de la tuberculose. À partir de ce risque, le coût de prévention d'un cas de tuberculose a été déterminé pour chaque groupe. RÉSULTATS: L'incidence cumulative de la tuberculose chez 11 698 personnes après un premier TST positif était de 6, 2 %. La densité de l'incidence variait selon l'origine ethnique (0, 6 – 15, 2), l'âge (2, 4 – 33, 9), le sexe (4, 7 à 9, 2) et l'intervalle (récent ou lointain) entre le test et la survenue de de la tuberculose active (1, 3 – 1667). Le coût de prévention d'un cas de tuberculose chez les personnes non autochtones ≥ 20 ans dont l'infection est survenue dans un passé lointain comparativement au personnes autochtones < 20 ans dont l'infection est survenue récemment était plus élevé par un facteur > 200. CONCLUSIONS: L'évolution d'un premier test TCT positif vers la tuberculose variait en fonction de l'âge, de l'ethnicité et de l'intervalle entre le TCT positif et la tuberculose mais ne variait pas en fonction du sexe. Le coût de prévention d'un cas de tuberculose variait inversement. L'utilisation de données épidémiologiques locales est utile et simple pour quantifier le risque de tuberculose et le coût de la meilleure prévention pour chaque dollar dépensé.